Factors affecting the accuracy of cost estimate in construction projects: a review - Faten, Albtoush; Doh, Shu Ing; Abdul Rahimi, Abdul Rahman; Ja’far A., Aldiabat Al-Btoosh; Syeda Maria, Zaidi (2020)
Construction sector considered as an important sector in most countries, which needs special attention since it is an important part of the growth of the local economy in most countries. The most important stage in construction project is cost estimation process. It is considered as a key of any construction project where it helps the client to decide to either proceed or not with the project. The cost estimation should be well prepared by the quantity surveyor or financial controller prior to the commencement of the project. In order to prepare sound cost estimation, the major factors that may affect the cost estimation should be identified. This paper reviews the factors affect the cost estimation in construction project in different countries namely New Zealand, Nigeria, Peninsular Malaysia and Gaza Strip. The result of the current paper revealed that the most significant factors affect the cost estimation in construction projects found in most of the countries are limited time to prepare estimate due to dateline, inaccuracy and unreliable cost information, unclear detail drawings and specifications, inexperience estimator, incomplete cost information, construction type and location of project.